Development of a core outcome set for paediatric achalasia: a joint ERNICA, ESPGHAN and EUPSA study protocol - Simon Eaton; Nigel J Hall; Frederic Gottrand; Jonathan J Neville; Iris den Uijl; Willemijn Irvine (BMJ Paediatrics Open)
Introduction Achalasia is a rare disease in children. Studies investigating the efficacy of interventions and disease outcomes in paediatric achalasia are predominantly retrospective, consist of small cohorts and report heterogeneous outcomes. The variation in the use and definition of reported outcomes impedes meta-analysis, which is problematic in a rare paediatric condition. Similarly, there is a risk of under-reporting patient-relevant outcomes, such as quality of life. To overcome these issues, a minimum set of important and patient-relevant outcomes should be reported in all studies of paediatric achalasia. Core outcome sets (COS) are a standardised set of outcomes that can guide further research and facilitate data pooling and meta-analysis. The development of a COS in rare paediatric disease is essential, prior to conducting efficacy studies or creating a disease registry, to ensure that the most important outcomes are reported. Currently, no COS exists for children with achalasia. In this study, we aim to define a COS for paediatric achalasia for use in clinical research.Methods and analysis This study will consist of three parts. The first will be a systematic review of the literature, evaluating the outcomes and outcome definitions reported in published clinical research studies investigating paediatric achalasia. Second, a three-stage Delphi consensus process will be undertaken to identify and prioritise outcomes. This process will involve healthcare professionals, patients and parent representatives. Third, a consensus meeting will be held, during which the final COS will be defined.Dissemination The results of this study will be disseminated to stakeholders via the European Reference Network for Rare Inherited Congenital Anomalies, European Society for Pediatric Gastroenterology Hepatology and Nutrition, European Paediatric Surgeons’ Association, and patient groups. The COS will be published in a peer-reviewed journal and uploaded to the Core Outcome Measures in Effectiveness Trials (COMET) initiative website.Trial registration number The study was pre-registered with the COMET initiative in July 2024 (https://www.comet-initiative.org/Studies/Details/2568). The systematic review component of the study was pre-registered on PROSPERO (CRD42024509855).